(untitled) (Journal of Asian Development Studies, 2026)
his study examines the relationship between external debt and capital flight in developing countries using a panel dataset of 78 countries spanning 2000–2024. The study is motivated by the persistent reliance of developing economies on external borrowing to finance investment and development, alongside the growing concern that increasing external debt may stimulate capital outflows rather than support domestic capital accumulation. Drawing on the debt-driven capital flight hypothesis, the study argues that rising external debt increases expectations of future macroeconomic instability, taxation, inflation, and repayment risk, thereby encouraging residents to transfer assets abroad. Methodologically, the study employs a comprehensive panel econometric framework. After conducting descriptive statistics and correlation analysis, the study tests for cross-sectional dependence, panel unit roots, slope heterogeneity, and cointegration. Given the presence of cross-sectional dependence and heterogeneous slope coefficients, the study applies the Method of Moments Quantile Regression (MM-QR) as the main estimator and Bootstrap Quantile Regression (BS-QR) as a robustness check. This approach allows examination of how the impact of external debt varies across levels of capital flight. The findings reveal that external debt significantly increases capital flight, with the effect becoming stronger at higher quantiles of capital flight. This suggests that external borrowing exerts a more harmful influence on countries already experiencing elevated capital outflows. The results also show strong persistence in capital flight, indicating that past outflows contribute to future outflows. In addition, economic growth and financial development reduce capital flight, whereas political stability generallyexerts a negative but weaker effect. The study concludes that poorly managed external borrowing contributes to capital flight in developing countries and highlights the need for prudent debt management, stronger institutions, and improved domestic financial conditions to retain capital and support sustainable development.